Multifunctional polymeric nanoparticles doubly loaded with SPION and ceftiofur retain their physical and biological properties - Solar, Paula (J Nanobiotechnology, 2015)
BACKGROUND: Advances in nanostructure materials are leading to novel strategies for drug delivery and targeting, contrast media for magnetic resonance imaging (MRI), agents for hyperthermia and nanocarriers. Superparamagnetic iron oxide nanoparticles (SPIONs) are useful for all of these applications, and in drug-release systems, SPIONs allow for the localization, direction and concentration of drugs, providing a broad range of therapeutic applications. In this work, we developed and characterized polymeric nanoparticles based on poly (3-hydroxybutyric acid-co-hydroxyvaleric acid) (PHBV) functionalized with SPIONs and/or the antibiotic ceftiofur. These nanoparticles can be used in multiple biomedical applications, and the hybrid SPION–ceftiofur nanoparticles (PHBV/SPION/CEF) can serve as a multifunctional platform for the diagnosis and treatment of cancer and its associated bacterial infections. RESULTS: Morphological examination using transmission electron microscopy (TEM) showed nanoparticles with a spherical shape and a core-shell structure. The particle size was evaluated using dynamic light scattering (DLS), which revealed a diameter of 243.0 ± 17 nm. The efficiency of encapsulation (45.5 ± 0.6% w/v) of these polymeric nanoparticles was high, and their components were evaluated using spectroscopy. UV–VIS, FTIR and DSC showed that all of the nanoparticles contained the desired components, and these compounds interacted to form a nanocomposite. Using the agar diffusion method and live/dead bacterial viability assays, we demonstrated that these nanoparticles have antimicrobial properties against Escherichia coli, and they retain their magnetic properties as measured using a vibrating sample magnetometer (VSM). Cytotoxicity was assessed in HepG2 cells using live/dead viability assays and MTS, and these assays showed low cytotoxicity with IC(50) > 10 mg/mL nanoparticles. CONCLUSIONS: Our results indicate that hybrid and multifunctional PHBV/SPION/CEF nanoparticles are suitable as a superparamagnetic drug delivery system that can guide, concentrate and site–specifically release drugs with antibacterial activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12951-015-0077-5) contains supplementary material, which is available to authorized users.